Structure and Microhardness of Cu-Ta Joints Produced by Explosive Welding - Iu. N. Maliutina; V. I. Mali; I. A. Bataev; A. A. Bataev; M. A. Esikov; A. I. Smirnov; K. A. Skorokhod (The Scientific World Journal)
The structure and microhardness of Cu-Ta joints produced by explosive welding were studied. It was found that, during explosive welding, an intermediate layer 20⋯40 μm thick with a finely dispersed heterophase structure, formed between the welded copper and tantalum plates. The structure of the layer was studied by scanning and transmission electron microscopy. Microvolumes with tantalum particles distributed in a copper matrix and microvolumes of copper particles in a tantalum matrix were detected. The tantalum particles in copper have a size of 5⋯500 nm, with a predominance of 5⋯50 nm particles. A mechanism for the formation of the finely dispersed heterophase structure in explosive welding is proposed. The microhardness of interlayers with the heterophase structure reaches 280 HV, which far exceeds the microhardness of copper (~130 HV) and tantalum (~160 HV). Many twins of deformation origin were found in the structure of the copper plate. The effect of heating temperature in the range from 100 to 900∘C on the microhardness of copper, tantalum, and the Cu-Ta welded joint was studied. Upon heating to 900∘C, the microhardness of the intermediate layer decreases from 280 to 150 HV. The reduction in the strength properties of the weld material is mainly due to structural transformations in copper.